Navigating Sustainable Consumption under Saudi Environmental Law: (Moral Conviction, Institutional Trust, and Cultural Negotiation among The Saudi Generation Z) - Dr. Nada Gurmalla Abdullah Algamdy (Journal of Arts, Literature, Humanities and Social Sciences, 2026)
Sustainable consumption has become a cornerstone of environmental policy worldwide, yet the translation of sustainability awareness into consistent consumer behavior remains a persistent challenge. This qualitative study explores the perceptions and lives experiences of young Saudi consumers in relation to sustainable consumption and the emerging Saudi environmental legal framework. Based on twenty semi-structured interviews, the findings reveal six key barriers: Legal perception and institutional trust, cultural traditions and the paradox of generosity, structural and market constraints, selective commitment and moral conviction, legal perception and institutional trust. These factors illustrate a disconnect between individual environmental concern and structural enablers that could support sustainable consumer behavior. Theoretically guided by the Theory of Planned Behavior (TPB), the study situates personal attitudes and perceived behavioral control within the broader regulatory context of Saudi Arabia’s environmental law reforms under “Vision 2030”. The findings highlight a critical policy gap: while environmental regulations have advanced rapidly, enforcement mechanisms, market incentives, and cultural interventions remain insufficient to foster behavioral change among young consumers. The study contributes to the dialogue on consumer sustainability and environmental governance by emphasizing the need for legal, educational, and market-oriented strategies that jointly encourage sustainable lifestyles among the next generation of Saudi citizens.